APPLICATION OF THE NINE-COMPONENTS INDICATOR MODIFIED TECHNIQUE FOR DIAGNOSTICS OF LEVEL OF THE FINANCIAL SAFETY OF THE ENTERPRISE - V. Kuzomko; M. Mykhailiuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In article it is carried out modification of calculation procedure of the nine-components indicator of the financial stability in the context of introduction of the indicators, which estimate accounts payable and stocks. Testing methods offered by financial diagnosis made on materials PJSC "Yahotyn creamery." The method of calculation of sixteen-components indicator of financial stability allows for a deeper analysis of enterprise financial stability and detect problems with production and inventory, as well as mid-term payables, which is not technique allows nine- components indicator of financial stability.